THE INFLUENCE OF BRAND AND SPICY LEVEL ON CONSUMER REPEAT ORDERS AT NOODLES GACOAN PAMEKASAN RESTAURANT - Dwiaryanti, Risca; Megawati, Normala; Hafidurrahman, Moh. (PT. Altin Riset Publishing, 2025)
This study aims to examine whether the brand and spicy level can affect consumer repeat orders at Noodles Gacoan Pamekasan Restaurant and to find out how much the brand and spicy level can affect consumer repeat orders. This research was carried out using a quantitative method. The population in this study is all consumers of Noodles Gacoan Pamekasan Restaurant and the sample was taken from a population of 50 respondents using the Simple Random Sampling technique. The data collection instrument for this study is a questionnaire. The research hypothesis test was carried out using testing of questionnaire data instruments in the form of validity tests, reliability tests, multiple linear regression analysis, t-tests, f tests, and determination coefficient tests. The data processing technique uses the SPSS software program (version 16.0). The results showed that the brand and spicy level had a significant stimulant effect on consumer repeat orders based on the t-test with a significant level of 0.041 < 0.05. This proves that Ho was rejected and Ha was accepted. Meanwhile, based on the results of the coefficient test, the determination of the magnitude of brand influence and spicy level on consumer repeat orders, it can be seen from the results obtained, that the terminated coefficient value (R2) shows an R square value of 0.977, which means that the amount of brand contribution and spicy level to consumer repeat orders is 97.7% while the remaining 2.3% is the contribution of other variables that are not included in this study. From the data interpretation table, the r-value is calculated in a series of numbers 0.80-0.1000 with a very strong interpretation.